From free-route air traffic to an adapted dynamic main-flow system. (June 2020) - Gerdes, Ingrid; Temme, Annette; Schultz, Michael
Graphical abstract: Highlights: Efficient method to identify main traffic flows in unstructured free route traffic. Usability enhancement of free routing by structural adaptations. Intersections of trajectories used as main characteristic of traffic flows. Efficient adaptation of free route traffic to a structured main flow system. Development of a new metric to quantify the structural complexity of traffic flows. Abstract: At present, en-route flight traffic is carried out on a system of predefined routes with a low number of intersections between aircraft trajectories. This enables the air traffic controllers to control and supervise the traffic, especially around these intersections. Consequently, the route system leads to a low ratio of used to unused airspace, where not necessarily the shortest route is used for each flight. To reduce trajectory length, the idea of free routing has been developed, whereby each aircraft uses the direct connection between origin and destination airport, generating a traffic distribution which uses nearly the entire available airspace. As a consequence, many intersections between flight trajectories occur, making it more difficult for controllers to handle. We use these intersections as the basis of a so-called main-flow system with trajectories consisting of intersection points instead of waypoints. The intersections of all trajectories of a traffic sample are clustered and the resulting cluster centres are used as nodes in a route system. Additional processing is applied to identify a system of main flows and reduce the number of intersections to an acceptable amount. Our approach is able to identify major traffic flows within unstructured great-circle traffic and to create a main-flow system which is a compromise between the flexibility of free routing and the easier surveillance by controllers in the case of a predefined route network. To prove the ability of the proposed method to identify main flows, it was applied to a scenario of planned flights following the standard route structure. Subsequent tests with two different free-routing scenarios led to new route systems where the median adapted trajectory length for flights of the traffic sample is merely 0.9% (respectively 4.1%) higher than the direct connections. Furthermore, structural complexity is lower for intersections (cluster centres) of the new main-flow system compared to those of direct or great-circle scenarios.